Electrospun transition/alkaline earth metal oxide composite nanofibers under mild condition for hydrogen evolution reaction. (24th August 2016) - Wu, Cong; Li, Junbo; Zhang, Dan; Yang, Boyu; Li, Lili; Zhou, Tingting; Zhang, Chunyan; Yang, Guocheng; Shan, Yuping
Abstract: Transition/alkaline earth metal oxide composite nanofibers (TAMNs) Ca3 Co4 O9 and MgCo3 O5 as a new class of oxide materials for hydrogen evolution were successfully fabricated by electrospinning followed by calcinations under mild condition, and characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), high resolution transmission electron microscope (HR-TEM), Raman spectroscopy, X-ray powder diffraction (XRD) and electrochemical method. The layered Ca3 Co4 O9 and MgCo3 O5 nanofibers (NFs) have promising capabilities as electrocatalyst for hydrogen evolution, exhibit low Tafel slope of 76 and 98 mV/decade for hydrogen evolution reaction (HER). The affordability and electrocatalytic properties have endowed TAMNs as a potential replacement for precious metal in electrocatalytic applications. Highlights: Transition/alkaline earth metal oxide composite nanofibers (TAMNs) Ca3 Co4 O9 and MgCo3 O5 were prepared by electrospinning. Ca3 Co4 O9 and MgCo3 O5 nanofibers show excellent electrocatalysis toward hydrogen evolution. The Ca3 Co4 O9 produces a small slope of 76 mV/decade for HER.